PENGARUH BRAND AWARENESS TERHADAP CUSTOMER LOYALTY DENGAN BRAND IMAGE DAN RELATIONSHIP QUALITY SEBAGAI VARIABEL INTERVENING PADA SEMEN GRESIK DI SURABAYA - Edo Karela Purwanto (Jurnal Strategi Pemasaran, 2016)
Countries Indonesia's economic growth is increasing, especially in infrastructure construction which is increasing in Surabaya. Cement industry took an important role in infrastructure development in the second largest metropolitan city. This study aimed to analyze the effect of through Brand Awareness ( Top of Mind Recall, Aided Recall, Spontaneous Recall) of Customer Loyalty (Customer Primary Behavior, Customer Secondary Behavior, Customer Intent to Repurchase) Brand Image ( Product Attributes, Consumer Benefits, Brand Personality), Relationship Quality (Behavioral Interpendence, Personal Commitment, Love and Passion, Nostalgic Connection, Self-Concept Connection, Intimacy, Partner Quality) as intervening variables. This study will be conducted by distributing questionnaires to 110 respondents store building who sell Semen Gresik. Analysis technique used is quantitative analysis techniques with methods of PLS (Partial Least Square).